DEFINITION OF CRIMES RELATED TO THE ILLEGAL TRAFFICKING OF PYROTECHNIC DEVICES IN THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN - Ilyosbek Tajaliyev (PT. Antis International Publisher, 2025)
Objective: This article examines the legal framework regulating crimes related to the illegal trafficking of pyrotechnic devices in Uzbekistan, emphasizing their impact on public safety and legal certainty. Method: Using a legal-analytical methodology grounded in doctrinal review, systematic analysis of legislation, and examination of law enforcement practice, the study identifies gaps in statutory provisions, procedural ambiguities, and weak inter-agency coordination. Result: Findings show that the classification of crimes by degree of social danger lacks clear boundaries between administrative and criminal liability, and expert examination regulations remain inadequately defined. Results also reveal that these shortcomings hinder effective prosecution and create legal uncertainty, reducing the preventive impact of criminal liability. Novelty: While existing studies discuss the general risks of pyrotechnics, this study addresses the knowledge gap concerning inconsistencies in the Criminal Code, particularly Article 250¹, and its uneven application in practice, thereby contributing original insights into the legal and institutional reforms needed to strengthen public safety.